(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The following article offers an instructional recommendation on how to teach spoken English grammar, which is crucial to achieving true language mastery. In order to clearly define spoken grammar, the theoretical framework must first be built. This includes an overview of the characteristics of spoken grammar as described by various authors. After that, this article looks at how to teach it and how to do so using audio-visual resources in the classroom. The intervention proposal is then described in terms of the goals, skills, and topics it aims to address, as well as the kind of methodology and evaluation it will use. Finally, a thorough explanation of the pedagogical concept is provided, outlining each session and activity that it has.